Effect of forest fire prevention treatments on bacterial communities associated with productive Boletus edulis sites - Mediavilla, Olaya; Geml, József; Olaizola, Jaime; Oria-de-Rueda, Juan Andrés; Baldrian, Petr; Martín-Pinto, Pablo (Microbial biotechnology, 2019)
Cistus ladanifer scrublands, traditionally considered as unproductive, have nonetheless been observed to produce large quantities of king bolete (Boletus edulis) fruitbodies. These pyrophytic scrublands are prone to wildfires, which severely affect fungi, hence the need for fire prevention in producing C. ladanifer scrublands. In addition, B. edulis productions have severely decreased in the last years. A deeper understanding of the B. edulis life cycle and of biotic and abiotic factors influencing sporocarp formation is needed to implement management practices that facilitate B. edulis production. For example, some bacteria likely are involved in sporocarp production, representing a key part in the triple symbiosis (plant-fungus-bacteria). In this study, we used soil DNA metabarcoding in C. ladanifer scrublands to (i) assess the effect of site history and fire prevention treatment on bacterial richness and community composition; (ii) test if there was any correlation between various taxonomic groups of bacteria and mycelial biomass and sporocarp production of B. edulis; and to (iii) identify indicator bacteria associated with the most productive B. edulis sites. Our results show that site history drives bacterial richness and community composition, while fire prevention treatments have a weaker, but still detectable effect, particularly in the senescent plots. Sporocarp production correlated positively with genera in Verrucomicrobia. Several genera, e.g. Azospirillum and Gemmatimonas, were identified as indicators of the most productive sites, suggesting a potential biological role in B. edulis fructification. This study provides a better understanding of the triple symbiosis (plant-fungus-bacteria) involved in C. ladanifer-B. edulis systems.
Keywords: mikrobiota; Cistus; Microbial Interactions; DNA Barcoding, Taxonomic; Microbiota; Soil Microbiology; metagenomika; Basidiomycota; taxonomické DNA čárové kódování; požáry v divočině; Metagenomics; Wildfires; Bacteria; mikrobiální interakce; půdní mikrobiologie